PENGARUH KINERJA INDIVIDU, KECANGGIHAN TEKNOLOGI, DAN KEMAMPUAN PENGGUNA TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI (STUDI KASUS PADA KANTOR PUSAT PT. POS INDONESIA KABUPATEN PATI) - Pricillia Pratma Antika; Junaidi Junaidi; Hariri Hariri (Universitas Islam Malang, 2020)
ABSTRACT This research was conducted with the aim of analyzing the audit quality of the ERC. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in the period 2015 - 2017. The samples in this study were 50 manufacturing companies produced during the period 2015-2017 on the Indonesia Stock Exchange. This study uses Audit Quality as an independent variable and Income Response Coefficient (ERC) as the dependent variable. The method of analysis uses Simple Linear Regression Analysis. Based on the analysis results obtained that audit quality has a significant effect on Earning Response Coefficient. (ERC) in Manufacturing companies in the period 2015 - 2017. Thus increasing the ERC value will improve Audit Quality. This research is expected to be a reference or consideration for company management in decision making and for investors to invest in a companyKeywords: Audit Quality, ERC and Manufacturing Companies